Jornadas Fadoc (XVIII) Fotografía y publicidad: aspectos informativos y documentales - Sánchez Vigil, Juan Miguel (Revista General de Información y Documentación, 2009)
Presentation of the conferences and lectures of the 18th Seminar of the Research and Documentation Faculty, dedicated to diverse informative and documentary aspects of Photography and Advertising. The contents were structured around four sessions: professional experiences, agencies and photo libraries, management and diffusion of photographs and their applications.
Keywords: Documentation; Photography; Advertising; Photographic Documentation; Advertising Documentation